The Class II KNOX gene KNAT7 negatively regulates secondary wall formation in Arabidopsis and is functionally conserved in Populus - Li, Eryang; Bhargava, Apurva; Qiang, Weiya; Friedmann, Michael C.; Forneris, Natascha; Savidge, Rodney A.; Johnson, Lee A.; Mansfield, Shawn D.; Ellis, Brian E.; Douglas, Carl J. (The New phytologist, 2012)
The formation of secondary cell walls in cell types such as tracheary elements and fibers is a defining characteristic of vascular plants. The Arabidopsis transcription factor KNAT7 is a component of a transcription network that regulates secondary cell wall biosynthesis, but its function has remained unclear. We conducted anatomical, biochemical and molecular phenotypic analyses of Arabidopsis knat7 loss-of-function alleles, KNAT7 over-expression lines and knat7 lines expressing poplar KNAT7. KNAT7 was strongly expressed in concert with secondary wall formation in Arabidopsis and poplar. Arabidopsis knat7 loss-of-function alleles exhibited irregular xylem phenotypes, but also showed increased secondary cell wall thickness in fibers. Increased commitment to secondary cell wall biosynthesis was accompanied by increased lignin content and elevated expression of secondary cell wall biosynthetic genes. KNAT7 over-expression resulted in thinner interfascicular fiber cell walls. Taken together with data demonstrating that KNAT7 is a transcriptional repressor, we hypothesize that KNAT7 is a negative regulator of secondary wall biosynthesis, and functions in a negative feedback loop that represses metabolically inappropriate commitment to secondary wall formation, thereby maintaining metabolic homeostasis. The conservation of the KNAT7 regulatory module in poplar suggests new ways to manipulate secondary cell wall deposition for improvement of bioenergy traits in this tree.